Morphometric sex estimation using mastoid triangle: A prospective study - Kiran, Meena; Shetty, Mahabalesh; Shetty, Suraj S; Shetty, Varsha (Journal of Indian Academy of Forensic Medicine, 2021)
In the evaluation of unidentified skeletal remains one important step is to estimate the sex of the remains. The morphometric analysis of the mastoid triangle for sex estimation in and around Mangaluru District was the objective of the study. The present study was conducted on 50 male and 50 female bodies subjected to medico-legal autopsy at Justice K. S. Hegde Charitable Hospital. The quantitative variables, and the area were expressed in terms of mean and standard deviation along with the utility of measurements which was evaluated for sensitivity and specificity of using ROC curve. The study confirms the low accuracy of the mastoid triangle with respect to sex estimation.